Rancang Bangun Aplikasi Manajemen Peralatan Pada Jurusan Pendidikan Teknik Elektro Berbasis Desktop - Dimas Vio Karim (JUKI : Jurnal Komputer dan Informatika, 2020)
The Department of Electrical Engineering Education is one of the majors at Universitas Negeri Medan. Universitas Negeri Medan has many tools to support its activities. At present, the Department of Electrical Engineering Education has an internal information system to control its equipment. The absence of equipment management applications will certainly experience difficulties in tracking down data tools. Solutions to overcome existing problems, of course, require equipment management information systems that can run equipment management to be more efficient and structured, and facilitate data collection tools. the method used in developing the system is a waterfall. This model consists of requirements analysis, system and software design, system and unit implementation, system testing, operation, and maintenance. With the application of equipment management, it will provide convenience in managing tool management in the Department of Electrical Engineering Education.